To the well: Malory's Sir Palomides on ideals of chivalric reputation, male friendship, romantic love, religious conversion-and loyalty - Holbrook, S.E. (Arthuriana, 2013)
Although Palomides in Malory's Morte Darthur and his counterpart in the French Tristan en Prose are usually discussed by their roles, my study selects five scenes linked by woodland settings, wells, and complaints. Accordingly, it demonstrates what each scene shows about the values of reputation, friendship, love, religious conviction, and-in the aftermath of the rupture between Lancelot and Arthur-the capacity for loyalty to Lancelot shown by Palomides and his brother Saphir. © 2013 Project MUSE.
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng